Sistem Informasi Penjualan Obat Pada Apotek Medan Rantauprapat - Tamba, Elprida Eleonora (Journal of Computer Science and Information System(JCoInS), 2022)
Medan Pharmacy is one of the pharmacies where data processing still uses recordings in general ledger and has not used computer technology optimally. As for the problems faced in processing data at Apotek Medan that is when buyers are crowded in the process of purchasing transactions, pharmacy guards incorrectly record or forget to record transactions that happened that day, this often results in imbalance of records between incoming goods and outgoing goods which ultimately report goods not balanced. In this study the method used is a method of data collection, namely literature study, observation, interviews, questionnaires,and the waterfall method. The results of this study are to produce a web-based drug sales information system as an effort to increase the effectiveness of entering drug data and finding drugs so that it can facilitate sales  transactions.